EFL Speaking Achievement in Undergraduate Oral Presentations: The Roles of Enjoyment and Self-Efficacy - Cenderato Cenderato; Exnasia Retno Palupi Handayani (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
English speaking achievement is a crucial outcome in foreign language learning, yet the interplay of affective factors like enjoyment and self-efficacy as determinant predictors remains an essential area for exploration. The purpose of this research is to determine the interrelationships among students’ English enjoyment, self-efficacy, and speaking achievement. Additionally, it also plays a mediating role in the relationship between self-efficacy and speaking achievement. The rationale for this investigation is rooted in developing more effective teaching strategies by understanding how positive emotions and confidence contribute to measurable language outcomes. This quantitative study employed a cross-sectional design involving undergraduate students at STAKat Negeri Pontianak. The sample included 102 students enrolled in the second semester. Data were collected using a speaking presentation test to measure achievement, along with validated questionnaires and semi-structured interviews to assess enjoyment and self-efficacy. The key findings revealed a positive prediction of speaking achievement when enjoyment and self-efficacy were considered together. The analysis underscored a moderate positive correlation, suggesting that self-efficacy had a moderate effect on speaking achievement. Crucially, the results provided evidence that enjoyment played a significant mediating role in the relationship between students’ self-efficacy and their speaking achievement. These findings carry significant pedagogical implications, suggesting that fostering positive emotions and enhancing student enjoyment is not merely a supplementary goal but a crucial factor that directly improves language learning outcomes. Teachers should focus on creating an emotionally supportive classroom environment to leverage this interplay for more effective foreign language speaking instruction.